The Effect Of Corn Flour Substituion On Cookies Quality - Lili Dasniati; Wirnelis Syarif (Jurnal Pendidikan Tata Boga dan Teknologi, 2020)
The background of this research is the use of local food ingredients in the manufacture of food using corn flour as an ingredient for making cookies. Corn is a source of carbohydrates that can be used as flour so that local natural resources can be better utilized. This type of research is an experiment with three repetitions. Primary data taken from 3 panelists by filling out a questionnaire and secondary data in the form of photos of the research process. The independent variable is cookies (X) and the dependent variable (Y) is the quality of the cookies, namely shape, color, aroma, texture, and taste. The data obtained were tabulated into tabular form and analyzed using ANOVA. The results showed that the average value of each quality was the best in uniform form X2 (3,7), corn form X3 (3,5), top color X3 (3 , 9), the bottom color of X3 (3,8), the aroma of corn X3 (2,7), the texture of X3 (3,6), the sweetness of X1 (3,7), the savory taste of X0 (3,4), and Corn flavor X3 (3,2).